A New Global Ionospheric Electron Density Model Based on Grid Modeling Method - Huijun Le; Tingwei Han; Qiaoling Li; Libo Liu; Yiding Chen; Hui Zhang (Space Weather)
Abstract Based on nearly 4.6 million radio occultation (RO) ionospheric profile data from Constellation Observing System for Meteorology, Ionosphere, and Climate satellites in 2006–2020, a global three‐dimensional ionospheric electron density model was constructed with a new concept. The global 3D ionosphere structure was divided into total 338,661 grids with longitude intervals of 10°, latitude intervals of 2°, and height intervals of 5 km. On each grid, the electron density is modeled as a function of solar activity, geomagnetic activity, local time, and season variation using 21 coefficients. Then all grid models are combined to form a global ionospheric model. This method makes full use of all ionospheric electron density data. The spatial resolution of the model is high with 10° in longitude, 2° in latitude, and 5 km in height, which can effectively model the fine ionospheric spatial structure like the longitudinal wavenumber‐4 structure in low latitudes. The model also takes into account the influence of both solar and geomagnetic activities on the ionosphere. At the altitude below the F2 peak, the RO electron density observation suffers from an artificial meridional maximum between the double peaks of the equatorial ionization anomaly, referred hereafter as the three‐peak error. By combining our model with the International Reference Ionospheric electron density results of the E layer below 140 km, the problem of three‐peak error is effectively solved. Compared the with other data sources such as the ZH01 and the ROCSAT‐1, the modeling ability of model in fine spatial structure is verified.